Tracking finance for locally led climate action in Kenya: Existing initiative, challenges and recommendations - Callaghan, Charles; Jalango, Dorcas; Binge, Brenda; Chilambe, Pedro; Lauriciano, Rabeca (2025)
The report summarizes Kenya’s current progress and gaps in tracking finance for locally led climate action, based on a document review and a multi-stakeholder workshop. It finds that while Kenya has begun strengthening national climate-finance transparency through climate budget tagging in IFMIS (Climate Change Budget Coding) and the development of a Climate Finance Information System (CFIS), it remains difficult to trace how much climate finance ultimately reaches counties and communities and how it is used. Major challenges include fragmented donor and government reporting requirements, limited technical capacity and awareness, non-mandatory reporting by many non-state actors, significant data gaps, risks of inconsistency or double counting, and delays that hinder timely reporting.